Single‐Crystalline Rhodium Nanosheets with Atomic Thickness. Issue 6 (8th May 2015) - Zhao, Li; Xu, Chaofa; Su, Haifeng; Liang, Jinghong; Lin, Shuichao; Gu, Lin; Wang, Xingli; Chen, Mei; Zheng, Nanfeng
<x xml:space="preserve">Abstract</x> CO confinement strategy for ultrathin Rh nanosheets: CO is introduced as a confining agent to regulate the anisotropic growth of unique 2D structure. The single‐crystalline Rh nanosheets have a thickness of three to five atomic layers and tunable edge length ranging from 500 to 1300 nm. By understanding the formation mechanism, surface‐clean Rh nanosheets are also prepared and display better catalytic performance that their surfactant‐capped nanosheets.